Internationalization strategy of Guava: Japan analysis - Caetano, Nuno Miguel Sobral Monteiro de Sousa (2018)
This work project was created to respond to Guava’s problem of what country they should try to expand to. Guava’s founder Inês had plans to explore five different markets, and Japan was the one I choose. To assess if this was the best choice for the company I did a country ranking analysis, followed by an internal analysis of Guava, external analysis of the market and how do firms expand, implementation plan on Japan, and then a financial analysis to check the NPV of this project. Finally consulted with an expert and reached the final conclusions and recommendations.